Effectiveness of acceptance and commitment therapy for distress, emotion regulation, and self-compassion in patients with cardiovascular disease: a randomized clinical trial - Arash Fattahi; Fatemeh Mazini; Nasrin Jaberghaderi; Fatemeh Rajabi; Mehdi Derakhshani; Mohammad Laki (Trends in Psychiatry and Psychotherapy)
Abstract Objective: Cardiovascular patients experience various psychological problems due to the conditions caused by their disease, making it worse if left untreated. The purpose of the current study was to evaluate the effects of acceptance and commitment therapy (ACT) on distress, emotion regulation, and self-compassion in patients with cardiovascular disease. Methods: This study was a randomized clinical trial with pre-test, post-test, and 2-month and 4-month follow-up periods accompanying a control group and an experimental group. Patients filled out questionnaires at four stages; a Depression, Anxiety, and Stress Scale (DASS-21), an Emotion Regulation Questionnaire (ERQ), and a Self-Compassion Scale (SCS). The experimental group underwent a treatment protocol based on ACT. Data were then analyzed using SPSS-25 with repeated measures analysis of variance (ANOVA). Results: ACT significantly reduced depression, anxiety, and stress, enhanced self-compassion, and improved emotion regulation in cardiac patients. Between-subjects (group) partial Eta squared (η²) for depression, anxiety, stress, reappraisal, suppression, and self-compassion were 0.61, 0.64, 0.66, 0.62, 0.66, and 0.65, respectively. Treatment efficacy was maintained at the 2-month and 6-month follow-up visits. Conclusion: The results of this study suggest that treating cardiac patients’ psychological problems in an ACT-focused manner may have an impact on how well they respond to their treatment.